Decolonization, Legitimacy and Fiscal Capacity: Event Study Evidence from Africa - Dhammika Dharmapala; Marvin Suesse (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
A vast literature across several academic disciplines studies the impact of colonial rule, but less attention has been paid to the consequences of decolonization. This paper uses a recently-constructed dataset on the fiscal history of African countries from 1900 to 2015 to analyze the impact of decolonization on fiscal capacity (defined as revenue from taxes that are relatively difficult to collect and that require more administrative infrastructure). The analysis adopts a staggered difference-in-difference approach, implemented using a stacked event study. It finds no discernible pre-trends prior to decolonization, and a substantial increase in fiscal capacity starting about 5-6 years after decolonization. This result – which implies substantial state-building activity in postcolonial Africa – is robust to tests for a variety of alternative explanations, the use of alternative control groups, and the use of generalized synthetic control methods. We also show that this effect is not explained by democratization or improved public goods provision. Our conceptual framework instead posits that post-colonial states were able to increase tax revenues from hard-to collect sources because their higher degree of legitimacy improved citizens' tax morale. We offer historical evidence that is consistent with this channel. Our finding – that colonial rulers invested less in fiscal capacity than did post-independence governments – sheds new light on the consequences of colonial rule, and on the determinants of variation in governments' fiscal capacity.
Keywords: H20; O12; N47; 330; taxation; colonialism; decolonization; fiscal capacity; legitimacy